Bis(4-carboxylpyrazol-1-yl)acetic acid: a scorpionate ligand for complexes with improved water solubility - Tzegai, Wintana; Reil, Michaela; Burzlaff, Nicolai (Dalton Transactions, 2022)
Bis(4-carboxylpyrazol-1-yl)acetic acid (H(3)bcpza) (2), obtained in a one-pot synthesis, contains carboxyl groups that differ in their pK(a) values. The ligand exhibits heteroscorpionate kappa(3)-N,N,O-coordination whereupon the peripheral carboxyl groups are not involved in metal binding. The corresponding carbonyl complexes [Mn(H(2)bcpza)(CO)(3)] (4), [Re(H(2)bcpza)(CO)(3)] (5) and [Ru(H(2)bcpza)Cl(CO)(2)] (6a/6b) are partially soluble in water but readily soluble in PBS buffer.
CRIS-Team WoS Importer:2022-05-06

p-Block metal complexes with bis(pyrazol-1-yl)acetato ligands - Pflock, Stephan; Langer, Frauke; Reil, Michaela; Strinitz, Lisa; Lorenz, Rebecca; Hubner, Eike G.; Burzlaff, Nicolai (Dalton Transactions, 2022)
The hetereoscorpionate ligands bis(pyrazol-1-yl)acetic acid (Hbpza) and bis(3,5-dimethylpyrazol-1-yl)acetic acid (Hbdmpza) are reacted with [Sn(OAc)(2)] or [Sn(acac)(2)] to yield the corresponding Sn(ii) complexes. A single crystal X-ray determination for the in solution monomeric complex [Sn(bpza)(2)] (1a) revealed a dinuclear molecular structure [Sn-2(bpza)(4)] (1b), with kappa(3)-N,N,O-coordinated bpza ligands at each of the Sn(ii) and two bpza ligands mu-bridging between the Sn(ii) centres. The molecular structure of [Sn(bdmpza)(2)] (2) exhibits a homoleptic bisligand complex with both ligands displaced by the free electron pair, which is proven by DFT calculations. Oxidation of complex 2 in an attempt to synthesize a homoleptic Sn(iv) complex leads to the formation of [Sn(bdmpza)F-3] (3). In addition, homoleptic bisligand gallium complexes [Ga(bdmpza)(2)][ClO4] (4) and [Ga(bpza)(2)][GaCl4] (5) were prepared and characterized by Ga-71 NMR and IR spectroscopy as well as by X-ray crystallography.
CRIS-Team WoS Importer:2022-03-04